Transformation of the Implementation of the Central Learning Model (BCCT) into a Stage Learning Model at the Pioneer Nature School of Bandung - Desika Putri Mardiani; Monica Widyaswari; Shobri Firman Susanto; Ali Yusuf (LP3M STAI MA'ARIF MAGETAN, 2023)
It is necessary to apply a suitable learning model for early childhood to explore every potential of students. Of course, learning media that are easy to find and local elements must be included so children can recognize themselves and know where they come from. The purpose of this study is to examine the transformation of the learning model into a stage learning model organized by PAUD Sekolah Pelopor Alam, Bandung. The research method uses a qualitative approach with data collection techniques in the form of interviews, indirect observation, and documentation. The data analysis used is Miles and Huberman analysis, while the validity test uses extension of observation, persistence of observation, and triangulation of sources. Research results showed that the implementation of early childhood education by applying the learning center model is less able to bring out the elements of localization in the Rancaekek, Bandung, so the founder switched to using the stage model, which is closer to the daily life of children. The stage model is inspired by the center model, which consists of several sub-sections. If the center model consists of a preparation center, an art center, a natural materials center, a beam center, and a role-play center. Whereas in the application of the stage model, There are eleven sub-sections developed, namely the stage of play, cooking stage, development stage, exploration stage, science stage, cooking stage, kasundaan stage, development stage, imtak stage, gardening stage, and livestock stage.